Determination and Confirmation of Boundaries for Dhawe Village, Aesesa District, Nagekeo Region using Cartometric Point Methods and High Resolution Satellite Images Acquisition in 2013 - Nanin Trianawati Sugito; Ryan Naufal Hamdani; Shalman AlghiFari Adriansyah; Farhan Zidni; Regina Vera Santiara Yahya Putri (Jurnal Pendidikan Geografi Gea, 2023)
Boundaries are one of the elements that must be depicted in a base map. The focus of this research is on boundaries or adjudication. Regional boundaries experience problems, including boundaries between villages that overlap between one village and another. Minister of Home Affairs Regulation Number 1 of 2017 concerning Village Structuring is the initiator in village structuring, however, there are still minimal regions structuring village authority through regional head regulations. Images are cropped to create indicative administrative map boundaries, a very important first step in regional boundaries. This research aims to determine and confirm the boundaries of Dhawe Village, Aesesa subdistrict, Nagekeo Regency in the context of implementing Permendagri Number 76 of 2012 in determining and confirming village boundaries, and aims to provide geospatial data in the form of village boundary coordinates. The method used in this research uses a cartometric method. After determining the boundary segment cartometry points, it produces 26 points which also contain the coordinates of Dhawe Village and produces agreed segment boundaries. Not only that, the researcher carried out a field approach test to test the correctness of the cartometry position so that the results could properly represent the expected village boundary area